Effect of polyester resin additive on the properties of asphalt binders and mixtures - Ahmedzade, Perviz; Yılmaz, Mehmet (My University, 2008)
The properties of AC-5 control asphalt binder, mixture containing the same asphalt were compared with the properties of AC-10 asphalt binder modi?ed by 0.75%, 1%, 2%, and 3% of polyester resin (PR), mixture containing pure AC-10 and AC-10 modi?ed by 0.75% of PR, respectively. Initial research was done to determine the physical properties of unmodi?ed and PR modi?ed asphalt binders. The AC-10 asphalt binder modi?ed by 0.75% of PR had good results compared to AC-5 control asphalt binder and all other modi?ed binders, and hence this modi?ed binder as well as unmodi?ed binders were used to prepare Marshall samples for Marshall stability and ?ow, indirect tensile sti?ness modulus (ITSM), indirect tensile strength (ITS) and creep sti?ness tests. The results of investigation indicate that AC-10 + 0.75% PR binder has better physical properties than AC-5 control asphalt binder and, at the same time, PR improves mechanical properties of asphalt mixture.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Bitumen; Polyester resin; Modified mixtures; Creep stiffness